Capital transnacional ¿el fin de los acuerdos sociales nacionales? La evolución reciente en Suecia. - Vernon, Guy; Rees, Chris (Cuadernos de Relaciones Laborales, 2001)
The paper challenges the per vasive view that economic inter nationalisation necessarily undermines national political * Skope, Oxford University, UK. ** School of HRM, Kingston University, UK. Artículo traducido por Beth Gelb. 149 Guy Vernon y Chris Rees Capital transnacional ¿el fin de los acuerdos sociales nacionales?... economies and renders unworkable state action in support of social protection and the social regulation of employment. Whilst it is commonly assumed that globalisation must erase the particularities of the so-called «Swedish model», a careful marshalling of the available evidence finds little support for the hollowing out or erosion of national regimes. On the contrar y, the paper presents a wide range of data (concerning employment, skill formation, earnings and inequality, bargaining activity, and corporate strategy) which shows evidence of continued specificity.
Keywords: industrial relations systems; economic internationalisation; convergence and diversity; Swedish model; social